Incidents in emergency medicine: Learning from 10 years of incident reporting Zwischenfälle in der Notfallmedizin: Lernen aus 10 Jahren „incident reporting“ - Weilbacher, Frank; Popp, Erik; St. Pierre, Michael; Neuhaus, Christopher (Notfall und Rettungsmedizin, 2023)
Background: Critical incident reporting systems (CIRS) are used to alert organizations of unknown and potentially safety-critical events, based on the idea that individuals can learn from other users’ experiences. Aim: The aim of this study was to analyze incident reports from CIRS-AINS relating to prehospital and/or resuscitation room/emergency department settings with regard to reported topics, and to identify recurring incident mechanisms. Materials and methods: All incident reports documented in CIRS-AINS between April 2010 and June 2019 were retrospectively analyzed. All reports from prehospital care, the resuscitation room or the emergency department were included. Elements of the reporting form and reported content were descriptively recorded and screened. In an iterative process, recurring elements were identified and incident reports categorized. Results: Of 6013 incident reports contained within the CIRS-AINS database, 198 met the inclusion criteria. The prehospital setting (n = 79, 39.9%) and resuscitation room were equally represented (n = 77, 38.9%). There were slightly fewer reports from the emergency department (n = 42, 21.2%). The most common problems were team conflicts/communication problems (30.2%), incidents involving medical devices (26.4%) and care transitions (15.1%). When looking at incident reports involving medical devices, patient monitors, defibrillators and respirators were most commonly involved. Conclusion: The results of this study might be useful for the design and focus of recurrent training. The relatively small number of CIRS-AINS reports with emergency medical content, together with potential underreporting, emphasizes the need for further promotion of CIRS as a valuable tool. This might potentially contribute to increased patient safety in prehospital and emergency medical settings.
CRIS-Team Scopus Importer:2023-09-22
Keywords: CIRS; Incident reporting; Patient safety; Risk management; Teaching and learning systems